Nitrogen-rich MOF derived porous Co3O4/N–C composites with superior performance in lithium-ion batteries. Issue 34 (10th August 2016) - Han, Xiao; Chen, Wen-Miao; Han, Xiguang; Tan, Yuan-Zhi; Sun, Di
Abstract : Porous Co3 O4 fish-scale structures with N-doped carbon coating were successfully fabricated via a simple N-rich Co-MOF templated chemical transformation at 500 °C in a nitrogen atmosphere. The sample exhibited excellent electrochemical properties as an anode material for LIBs. Abstract : Porous N-doped carbon coated Co3 O4 fish-scale structures were successfully fabricated via chemical transformation of a well-designed N-rich Co-MOF at 500 °C in a nitrogen atmosphere. Due to the synergistic effect between the assembled porous Co3 O4 nanoparticles and the N doped C coating, the sample exhibited excellent electrochemical properties as an anode material for lithium-ion batteries. The specific capacity can remain at a stable value of about 612 mA h g −1 at a current of 1000 mA g −1 within 500 cycles.